The role of probiotics in prevention and treatment of food allergy - Shimin Gu; Dong Yang; Chenglong Liu; Wentong Xue (Food Science and Human Wellness)
With the prevalence of food allergy increasing every year, food allergy has become a common public health problem. More and more studies have shown that probiotics can intervene in food allergy based on the intestinal mucosal immune system. Probiotics and their metabolites can interact with immune cells and gut microbiota to alleviate food allergy. This review outlines the relationship between the intestinal mucosal immune system and food allergy. This review also presents the clinical application and potential immunomodulation mechanisms of probiotics on food allergy. We aim at providing a reference for further studies to explore the key active substances and immunomodulation mechanisms of anti-allergic probiotics.